GE_GERICHTE A/589/2024 vom 29. Juni 2016 - GE Cour de justice (2016)
MESURE DE CONTRAINTE(DROIT DES ÉTRANGERS);DÉTENTION AUX FINS D'EXPULSION | LEI.75.al1.letb; LEI.76.al1.letb.ch1; LEI.76.al1.letb.ch3; LEI.76.al1.letb.ch4